A GLANCE AT EMOTIONAL INFLUENCE OF THE POETRY - Egamova, Nigora Ustamirzayevna (Educational Research in Universal Sciences, 2023)
This essay discusses poetry, how it came to be, the emotions that are reflected in it, and the poet’s role in expressing those emotions. It also uses examples to focus on the inner spiritual experiences that the poet expresses in the poem.